2011
DOI: 10.1016/j.tetlet.2011.07.102
|View full text |Cite
|
Sign up to set email alerts
|

Obionin B: an o-pyranonaphthoquinone decaketide from an unidentified fungus (MSX 63619) from the order Pleosporales

Abstract: A fungal extract (MSX 63619), from the Mycosynthetix library of over 50,000 fungi, displayed promising cytotoxicity against a human tumor cell panel. Bioactivity-directed fractionation led to the isolation of an o-pyranonaphthoquinone decaketide, which we termed obionin B (1). The structure of 1 was deduced via spectroscopic and spectrometric techniques. The IC50 value of 1 was moderate, ranging from 3 to 13 μM, depending on the cell line tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Based on previous studies and as part of our continued effort to quantify the chemical diversity of fungal isolates [6], herein we expand the analysis to a larger set of 207 compounds described by our group [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] that represent twice the size of the dataset analyzed in 2012. In the current analysis, we employed molecular fingerprints as distinct molecular representations not analyzed in the previous study; also we emphasized the evaluation of molecular complexity that may have a significant impact in drug discovery endeavors, since this feature has been associated with target selectivity (and potential toxicity).…”
Section: Special Focus Issue -Antifungal Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies and as part of our continued effort to quantify the chemical diversity of fungal isolates [6], herein we expand the analysis to a larger set of 207 compounds described by our group [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] that represent twice the size of the dataset analyzed in 2012. In the current analysis, we employed molecular fingerprints as distinct molecular representations not analyzed in the previous study; also we emphasized the evaluation of molecular complexity that may have a significant impact in drug discovery endeavors, since this feature has been associated with target selectivity (and potential toxicity).…”
Section: Special Focus Issue -Antifungal Drug Discoverymentioning
confidence: 99%
“…The largest fragments were kept, duplicates in each dataset were removed and all molecules with molecular weight (MW) over 1000 were excluded. The in-house library of fungal metabolites with 207 compounds (referred to hereafter as 'FUNGI') [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] was compared with the following five reference collections: 2249 compounds based on the Flavor and Extract Manufacturers Association of the United States GRAS list, updated to GRAS 27 (hereafter referred to as 'GRAS') [24,30]; FDA drugs obtained from DrugBank [31] containing: 76 drugs approved to treat cancer (hereafter referred to as 'FDA-ONC') and 1399 nononcological drugs (hereafter referred to as 'FDA-NONC'); 713 drugs in clinical trials reported by the Therapeutic Target Database [32] (hereafter referred to as 'CLINIC'); and 850 compounds from a commercial collection focused on epigenetic targets, available at Selleckchem (hereafter referred to as 'GENERAL') [33]. Supplementary Table 1 summarizes the number of duplicate molecules found in the initial datasets.…”
Section: General Approachmentioning
confidence: 99%
“…[34] DNA extraction, PCR amplification, sequencing, and phylogenetic analyses were performed as described previously. [1b, 35] BLAST search in GenBank and the curated BOLD systems (http://www.boldsystems.org/index.php/IDS_OpenIdEngine) database, as well as Q-bank using ITS rDNA sequences suggested that MSX45109 shared high sequence similarity with several Centraalbureau voor Schimmelcultures (CBS) strains of Setophoma terrestris (Pleosporales, Ascomycota) with ≥80% query coverage and 99–100% sequence identity. The top BLAST matches were downloaded using Seaview v4.4.2.…”
Section: Methodsmentioning
confidence: 99%
“…[1] The organic extract of a solid phase culture of Setophoma terrestris (MSX45109), which was isolated from plant material collected in a mangrove habitat in 1989, showed potent cytotoxic activities against the SW-620 (colon) and MDA-MB-435 (melanoma) cancer cell lines (~91% and 100% inhibition of cell growth when tested at 20 μg/mL, respectively). Of the hundreds of cultures that have been investigated as part of this project, S. terrestris was intriguing due to the robust biosynthesis of 16 polyketides ( 1 – 16 ) of distinct structural classes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation